A new coplanar design of a 4‐bit ripple carry adder based on quantum‐dot cellular automata technology - Saeid Seyedi; Behrouz Pourghebleh; Nima Jafari Navimipour (IET Circuits, Devices and Systems)
Abstract Quantum‐dot cellular automata (QCA) is one of the best methods to implement digital circuits at nanoscale. It has excellent potential with high density, fast switching speed, and low energy consumption. Researchers have emphasized reducing the number of gates, the delay, and the cell count in QCA technology. In addition, a ripple carry adder (RCA) is a circuit in which each full adder's carry‐out is the connection for the next full adder's carry‐in. These types of adders are quite simple and easily expandable to any desired size. However, they are relatively slow because carries may broadcast across the entire adder. Therefore, an RCA design on a nanoscale QCA is proposed to diminish the cell number, improve complexity, and decrease latency. The QCADesigner simulation tool is used to verify the correctness of the suggested circuit. The comparison results for the design indicate an approximately 49.14% improvement in cell number and 14.29% advantage in area for the state‐of‐the‐art 4‐bit RCA designs with QCA technology. In addition, the obtained results specify the effectiveness of the offered design.